DANCE AS A STRATEGY FOR PROMOTING CULTURAL PRODUCTS: LITERATURE REVIEW OF CHALLENGES AND OPPORTUNITIES FOR BATIK MSMEs IN INDONESIA - Taufik Murtono; Dwiyasmono Dwiyasmono; Rokhim Nur (Dian Nuswantoro University, 2025)
Batik MSMEs in Indonesia face significant challenges in promoting products based on cultural identity, especially in the era of globalization and digitalization, which encourages the homogenization of marketing strategies. One innovative alternative that has the potential to overcome this challenge is the use of dance as a symbol-based visual communication medium. This study aims to analyze the potential of dance in strengthening the promotion strategy of cultural products, especially batik, through a literature review approach to reputable scientific sources. The study result shows that dance, through movements, costumes, and visual expressions, can build a symbolic narrative that strengthens the cultural identity of batik products. The integration of visual elements from dance into promotional strategies can increase the emotional connection between products and consumers, create added value, and strengthen product images based on local wisdom in a competitive market. These findings contribute to a new conceptual framework for developing batik MSME promotion strategies by positioning performing arts as a relevant medium for building brand identity and strengthening the competitiveness of cultural products